2020
DOI: 10.1002/dmrr.3372
|View full text |Cite
|
Sign up to set email alerts
|

Co‐microencapsulation of human umbilical cord‐derived mesenchymal stem and pancreatic islet‐derived insulin producing cells in experimental type 1 diabetes

Abstract: Introduction Post‐partum umbilical cord Wharton Jelly‐derived adult mesenchymal stem cells (hUCMS) hold anti‐inflammatory and immunosuppressive properties. Human pancreatic islet‐derived progenitor cells (hIDC) may de‐differentiate, and subsequently re‐differentiate into insulin producing cells. The two cell types share common molecules that facilitate their synergistic interaction and possibly crosstalk, likely useful for the cell therapy of type 1 diabetes (T1D). Materials and methods Upon microencapsulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…If ISDs are not required following MSC transplantation, the associated medical care costs would be reduced while improving the patient quality of life [58]. It should also be noted that the development of IPC cell therapy requires the encapsulation of islet cells and nanotechnology that can safely deliver them and protect them against immune cells [59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If ISDs are not required following MSC transplantation, the associated medical care costs would be reduced while improving the patient quality of life [58]. It should also be noted that the development of IPC cell therapy requires the encapsulation of islet cells and nanotechnology that can safely deliver them and protect them against immune cells [59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…IPCs were induced using a modified three-step, 10-day version of the insulin-transferrinselenium (ITS) induction method first established in tonsil MSCs [60,66]. In step 1, hUC-MSCs and hAD-MSCs in high-glucose alpha-minimal essential medium (α-MEM; HyClone Laboratories, Logan, UT, USA) were seeded in an uncoated 90 mm × 15 mm dish (Nunc, Naperville, IL, USA) with bovine serum albumin (BSA; Sigma-Aldrich, St. Louis, MO, USA) without 1% fatty acids (Sigma-Aldrich, St. Louis, MO, USA), and ITS media supplement was added at 37 • C in a 5% CO 2 incubator for 2-day.…”
Section: Direct Trans-differentiation Of Huc-mscs and Had-mscs Into Ipcsmentioning
confidence: 99%
“…In sum, there is compelling evidence that multiple precursors exist that give rise to insulin‐secreting cells in humans 11–13 and hence can be exploited for cell therapy for diabetes. Recently, it has been found that co‐transplantation of human pancreatic islet‐derived progenitor cells together with MSCs derived from umbilical cord Wharton Jelly in microencapsulated alginate reverses hyperglycaemia in T1D mouse model 14 . These findings suggest the synergetic effect between both cell types in reversing hyperglycaemia of T1D model.…”
Section: Introductionmentioning
confidence: 90%
“…The study demonstrated the remarkable role of the ECM-like alginate microcapsule and the co-encapsulation of postpartum umbilical cord Wharton’s Jelly–derived adult MSCs in protecting insulin-producing cells from the host immune system. It also showed that transplantation of human pancreatic islet-derived progenitor cells alone worked within a specific time frame, while the prepared microsystem extended graft function for 180 days ( Montanucci et al, 2020 ).…”
Section: Hydrogel-based Encapsulation Devicesmentioning
confidence: 99%